The self-nano mixer effect: about homogeneity of tungsten in WxTayCr5Ni5Fe5Mo5 alloy for radiation shielding - Aygun, Murat; Karabulut, Ezman; Celik, Fatih Ahmet; Aygun, Zeynep; Yilmaz, Mucahit; Ercan, Ercan (Iop Publishing Ltd, 2025)
In the present study, the role of elements such as Ta (tantalum), W (tungsten) and Mo (molybdenum) in the alloys as well as standard elements such as Cr (chromium), Fe (iron) and Ni (nickel), was analyzed in more detail by using molecular dynamics study (MD) based density functional theory (DFT) for recently newly produced WxTayCr5Ni5Fe5Mo5 alloys. It was observed that the increase in the Ta/W ratio causes a decrease in radiation shielding feature since there is agglomeration of Ta elements among the W elements, as well as Ta is the less dense element. It is seen that this Ta agglomeration occurs when W elements are separated from each other by Mo, showing thermal stability. This prevents W elements from agglomerating. For this reason, the first solidification in the alloy in the cooling phase starts with Ta atoms. It was observed that the W-Mo duo in the nanostructure plays a mixer role in the alloy. Another feature in this simulation is that, since the agglomeration of W elements in the absence of the Ta element has a heterogeneous effect in the alloys, a strain softening structure is seen in mechanical property and thus the remainder of the material consists of low-density elements. So, the radiation shielding feature is negatively affected. W-Mo duo creates the homogenous dispersing role of W elements. This situation leads to the emergence of a new definition in materials science. This nano mixer effect, which belongs to the W-Mo duo, was described for the first time in this study. It is observed that the mixing effect of W-Mo duo can be effective up to the melting temperature of Mo. Also the effect of Pt-W duo, which creates the best homogeneity effect among transition metals, was also examined. The nano mixer effect of the Pt-W duo was found to be more effective than the Mo-W duo.
Keywords: thermal stability; nano-mixer effect; molybdenum; tantalum; tungsten; platinum